Analisis Penerapan ISO 9001: 2015 di Perguruan Tinggi: Narrative Literature Review - Desi Susanti; Vyka Nur Amalia (Journal of Information Systems and Management (JISMA), 2023)
The purpose of writing this article is a narrative literature review of 3 (three) articles that discuss the analysis of the application of ISO 9001: 2015 in Higher Education, aiming to identify and summarize articles that have been published previously without any criticism for the articles reviewed. The results of the review show at the stage of designing and developing an ISO 9001 standard quality management system, through the stages of planning, implementation, inspection and continuous improvement. The design and development of quality management systems is built through literature studies related to ISO 9001 requirements and all policies, manuals, guidelines, standards, work instructions in universities, as well as discussions with all leaders in Faculties, Departments, Study Programs and related Bureaus. The results of this study reveal that strong management and leadership commitment is not only one of the supporters of the effectiveness of the implementation of the ISO 9001 quality management system, but the need for financial resources, facilities, infrastructure and people is important to manage. Based on the f test, it was obtained that simultaneously all independent variables had a significant effect on the dependent variable of 53,863. Based on the regression test, it can be stated that ISO 9001: 2015 does not have a partial but simultaneous effect when integrated with motivation and competence variables. Quality Management uses control and assurance of product processes to achieve quality more consistently. The basic pattern of a quality management system (ISO 9001:2015) is what we will and after we do we write (planning and reports) and what we write we do which is better known as the P-D-C-A (Plan – Do – Check – Action) pattern. The concept of quality control is the basis for assessing the results to be achieved in the context of meeting customer needs and satisfaction.